PHYSIOCHEMICAL AND CYTOLOGICAL CHARACTERISTICS OF SYNOVIAL FLUID IN THE CARPAL JOINT OF MIXED-BREED GOATS CARACTERÍSTICAS FÍSICO-QUÍMICAS E CITOLÓGICAS DO LÍQUIDO SINOVIAL DA ARTICULAÇÃO DO CARPO DE CAPRINOS MESTIÇOS - Marcela Figueredo Duarte Moraes; Paulo José Duarte Neto; Maria Isabel Souza; Janaína Azevedo Guimarães; José Wanderley Cattelan; Carla Lopes Mendonça; Daniela Oliveira (Ciência Animal Brasileira, 2010)
The carpal joint in goats is subject to diseases such as caprine arthritis encephalitis, leading to pain and a reduction in movement. Due to the scarce records of normal parameters, the aim of the present study was to assess the physiochemical and cytological make up of the synovial fluid in the carpal joint of 44 mixed-breed goat without joint disease. The following physiochemical characteristics were assessed: volume (0.94mL ± 0.26 mL), color (colorless to yellow), turbidity (46.50% were limpid), mucin precipitation (firm coagulant in limpid solution) and concentration of total proteins (1.95 ± 0.87 mg/dL). Cytological assessment consisted of global and differential leukocyte counts. The mean global count was 48.02 ± 24.47 cells/µL. The differential count was 25.07 ± 15.86 lymphocytes/µL and 16.31 ± 12.63 large mononucleated cells/µL. It is suggested that the parameter values obtained in the present study may be considered normal for synovial fluid in the carpal joint of adult mixed-breed goats. KEY WORDS: Carpus, goat, joint, synovia. A articulação do carpo dos caprinos é alvo de enfermidades, como a artrite-encefalite caprina, levando à dor e à redução dos movimentos. Devido à falta de registro de parâmetros normais, este estudo avaliou a constituição físico-química e citológica do líquido sinovial da articulação do carpo de 44 caprinos sem raça definida, que não apresentavam doença articular. Os parâmetros físico-químicos avaliados foram volume (0,94 mL ± 0,26 mL), cor (incolor a amarelo), turbidez (46,50% apresentaram-se límpidas), precipitado de mucina (coágulo firme em solução límpida) e concentração de proteínas (1,95 ± 0,87 mg/dL). Os dados citológicos corresponderam às contagens global e diferencial de leucócitos. A contagem global média encontrada foi de 48,02 ± 24,47 células/µL e contagem diferencial com 25,07 ± 15,86 linfócitos/µL e 16,31 ± 12,63 grandes células mononucleadas/µL. Sugere-se que os valores obtidos nesta pesquisa sejam considerados parâmetros normais para o líquido sinovial do carpo de caprinos adultos sem raça definida. PALAVRAS-CHAVES: Articulação, caprino, carpo, sinóvia.